2019
DOI: 10.3390/sports7060149
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Exercising and Associations with Body Composition in Icelandic Adolescents

Abstract: The aim of this study is to identify and analyze the motives that lead Icelandic teenagers to engage in physical exercise and the possible associations with variables of their body composition. For this purpose, the Self-Report of Reasons for the Practice of Physical Exercise questionnaire (AMPEF) was administered to 387 students (54% boys and 46% girls, Mage = 13.38 years) from Reykjavik (Iceland). The results reveal the subscales Revitalization and Enjoyment, Strength and Endurance, Challenge and Competition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…At the other end of the scale, the motives which generated the least interest in pupils in practising physical exercise were social recognition, and health emergencies. The same results have been obtained in other studies [39,40,42].…”
Section: Discussionsupporting
confidence: 91%
“…At the other end of the scale, the motives which generated the least interest in pupils in practising physical exercise were social recognition, and health emergencies. The same results have been obtained in other studies [39,40,42].…”
Section: Discussionsupporting
confidence: 91%
“…Since CRAE training is able to combine multiple different exercise modalities, it may be more enjoyable and less demanding in these young individuals compared to AE or RT alone. This notion can be supported by previous studies that reported adolescents of various backgrounds have stated that they would be more inclined to engage in exercise if it is perceived as fun and enjoyable [ 143 , 144 , 160 ]. Studies about specific exercise modality, and adherence rate are warranted to develop optimal exercise modalities for pediatric populations.…”
Section: Exercise Modality and Prescriptionsupporting
confidence: 61%
“…Several also noted, some with pride, that they did not mind the intensity of the exercise, although it was moderate to vigorous maybe because hyperactivity was a component of our sample given that 75% of the participants had ADHD. Finding the exercise enjoyable has been found to be a main motive to exercise [27,28].…”
Section: Discussionmentioning
confidence: 99%